2019
DOI: 10.15448/1980-8623.2019.1.28800
|View full text |Cite
|
Sign up to set email alerts
|

O impacto do esporte competitivo na escolha alimentar: narrativas de atletas de ginástica artística masculina

Abstract: Esportes que supervalorizam a estética e o baixo peso corporal são indicados como os com mais incidência de comportamentos alimentares de risco. Diante disto, investigou-se o impacto do esporte competitivo na escolha alimentar de atletas de ginástica artística masculina e, para tanto, foram entrevistados quatro ginastas adultos do gênero masculino. Trata-se de um estudo transversal, com o uso das narrativas como abordagem metodológica. As entrevistas foram obtidas por meio de questões abertas e analisadas à lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It can be suggested that fitness practitioners already begin the practices at the gym dissatisfied with the body image and, as a consequence, develop risk behaviors for the EDs [6]. Past studies argue that the commitment and frequency of the practice are factors that contribute to the adoption of EDs [30,61]. Thus, it can be inferred that the difference found in the present study can also be explained by the amount of training of the fitness practitioners, since they practice 3 to 5 times a week, whilst crossfit practitioners take the practices 2 to 3 times a week.…”
Section: Discussionmentioning
confidence: 99%
“…It can be suggested that fitness practitioners already begin the practices at the gym dissatisfied with the body image and, as a consequence, develop risk behaviors for the EDs [6]. Past studies argue that the commitment and frequency of the practice are factors that contribute to the adoption of EDs [30,61]. Thus, it can be inferred that the difference found in the present study can also be explained by the amount of training of the fitness practitioners, since they practice 3 to 5 times a week, whilst crossfit practitioners take the practices 2 to 3 times a week.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the results found show that compromise to the exercise is one of the factors contributing to the development of disorder of body image 10,11 . Belief confirmed at verifying that CrossFit competitors have shown higher indicative of muscular dysmorphia when compared to recreational athletes.…”
Section: Discussionmentioning
confidence: 99%